1994
DOI: 10.1007/bf00019055
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced formation of pheophytin/chlorophyll-containing complexes during the greening of plant leaves

Abstract: Illumination of etiolated maize leaves with low-intensity light produces a chlorophyll/pheophytin-containing complex. The complex contains two native chlorophyll forms Chl 671/668 and Chl 675/668 as well as pheophytin Pheo 679/675 (with chlorophyll/pheophytin ratio of 2/1). The complex is formed in the course of two successive reactions: reaction of protochlorophyllide Pchlde 655/650 photoreduction resulted in chlorophyllide Chlde 684/676 formation, and the subsequent dark reaction of Chlde 684/676 involving M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 16 publications
0
12
2
Order By: Relevance
“…Regardless of the degree of Pchlide 655/650 phototransformation, the ratio of Pheo and Chl concentrations remained constant under continuous lowintensity illumination (Ignatov and Litvin 1994). This observation seemed to be at variance with the data on the fast transformation of Pheo into Chl, observed in experiments with alteration of light and dark periods (see above).…”
Section: Photoinduced Transformation Of Chlorophyll Chl 671/668 Into contrasting
confidence: 54%
See 1 more Smart Citation
“…Regardless of the degree of Pchlide 655/650 phototransformation, the ratio of Pheo and Chl concentrations remained constant under continuous lowintensity illumination (Ignatov and Litvin 1994). This observation seemed to be at variance with the data on the fast transformation of Pheo into Chl, observed in experiments with alteration of light and dark periods (see above).…”
Section: Photoinduced Transformation Of Chlorophyll Chl 671/668 Into contrasting
confidence: 54%
“…From these data it may be concluded that Pheo formed from Chlide 684/676 during further dark reactions is transformed into chlorophyll. It was previously shown that the intermediates as well as products of dark transformation of Chlide 684/676 are esterified (Ignatov and Litvin 1994).…”
Section: Dark Reaction Of the Pheo 679/675 Transformation Into Ch1671mentioning
confidence: 99%
“…20,21 However, the Pheo a/Chl a ratio, which they estimated from the fluorescence excitation spectra, was as high as 50%, which is far from the value obtained here (about 0.47%). Such a discrepancy might, at least partially, be due to a difference in the illumination conditions.…”
Section: Discussioncontrasting
confidence: 95%
“…In our experiments, PChlide accumulated in the dark was almost completely photo-reduced to Chlide a by illumination (data not shown), but only 5 to 30% of PChlide was photo-reduced in the experiments of Ignatov and Litvin. 20 Under greening conditions where the amounts of Chl(ide) a are limited, Pheo a might be preferentially accumulated. Further experiments are required to clarify the discrepancy between the two experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that the pheophytin a associated with PS II reaction centers is formed by the spontaneous loss of the during insertion of chlorophyll a into the reaction center complex. However, recent studies in higher plants (Litvin et al, 1993;Ignatov and Litvin, 1994) suggest that pheophytin a formation may proceed directly from minor, long-wavelength chlorophyll precursors (e.g., the chlorophyllide precursor, P650).…”
Section: G Reaction Center Chlorophylls and Pheophytinmentioning
confidence: 97%